2019
DOI: 10.1111/ane.13057
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis epidemiology in Finland: Regional differences and high incidence

Abstract: Objectives Studies on the east‐west gradient of multiple sclerosis (MS) are scarce. In Finland, epidemiological differences have been only partially elucidated, but the MS risk is high, and it has been claimed that the occurrence follows a longitudinal gradient. In this register‐based study, we updated the MS epidemiology in southwest Finland (SwF) and compared it to the easternmost hospital district, North Karelia (NK), for which no previous data exist. Materials and methods Patients with ICD‐10 code G35 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
(44 reference statements)
3
19
0
Order By: Relevance
“…A special epidemiological feature in Finland observed already in 1970s concerns the regionally high MS prevalence in coastal parts of Western and South‐Western Finland . The difference between South‐Western and Eastern Districts shown already in 1970s prevailed in a study in 2016, where a 5‐year follow‐up from 2012 to 2016 showed age‐standardized rates 280/10 5 (95% CI 264‐296) and 168/10 5 (95% CI 148‐190), respectively . Difference between coastal and inland districts was shown to prevail also in our data.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A special epidemiological feature in Finland observed already in 1970s concerns the regionally high MS prevalence in coastal parts of Western and South‐Western Finland . The difference between South‐Western and Eastern Districts shown already in 1970s prevailed in a study in 2016, where a 5‐year follow‐up from 2012 to 2016 showed age‐standardized rates 280/10 5 (95% CI 264‐296) and 168/10 5 (95% CI 148‐190), respectively . Difference between coastal and inland districts was shown to prevail also in our data.…”
Section: Discussionsupporting
confidence: 77%
“…Finland is located between latitudes 60° and 70°N, and longitudes 20° and 32°E, and it is one of the world's northernmost countries. Epidemiological data updated in 2016 showed a high nationwide MS crude prevalence estimate of 180‐200/10 5 and east‐west gradient . Incidence trends from 1981 to 2010 in the Province of Western Finland in Tampere University Hospital District showed a significant increase among women and opposite trends in increasing relapsing‐remitting onset MS (RRMS) and decreasing primary progressive (PPMS) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine vitamin D supplementation for pregnant women was introduced in 2004, providing a natural trial of vitamin D supplementation and the impact on MS incidence. Incidence rates for MS in southwest Finland were 5.1, 5.2, and 11.6 per 100 000 for the hospital districts of Uusimaa, Vaasa, and Seinajoki, respectively, from 1979 to 1993, and 12.1 per 100 000 for southwest Finland in 2012–2016 . This is not the dramatic reduction in MS incidence that might have been expected with the advent of vitamin D supplementation.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 87%
“…Finland is a high-risk MS region with a prevalence of 280/100,000 in southwest parts of the country [13], and a nationwide prevalence estimate between 10,000 and 11,000 patients, corresponding to a crude prevalence of 180-200/100,000 [14]. The estimated annual economic burden of MS in Finland using a bottom-up approach of costing was €46,994 per patient on average and increasing from €10,835 to €109,901 in parallel with advancing disability [15].…”
Section: Introductionmentioning
confidence: 99%